2012
DOI: 10.5539/ies.v5n5p109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Teaching Performance of Student-teachers on Teaching Practice

Abstract: The study assessed teaching performance of 222 student-teachers from the Faculty of Education, Ekiti State University, posted to various secondary schools in Ekiti State for a six-week teaching practice during 2010/2011 academic session. The sample included 119 males, 103 females, 78 (300-Level) and 144 (400-Level) students. Data were collected using Teaching Performance Assessment Form designed by the Faculty of Education, Ekiti State University and analysed using frequency counts, percentages, item-total cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Peer Assessment (PA) in teacher education is a strategy for helping learners to examine their progress in teaching (Sluijsmans and Prins, 2006) and be familiar with it before teaching in classrooms (Wen and Tsai, 2008). Teaching practice is an exercise used to expose student teachers to the practical aspects of teaching (Oluwatayo and Adebule, 2012). Although teaching practice is essential in teacher education (Jian, Odell, and Schwille, 2008;Oluwatayo and Adebule, 2012), attempts to improve it through early assessment are not widely reported (Charalambous, Hill and Ball, 2011).…”
Section: Peer Assessment Of Performance In Teacher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Peer Assessment (PA) in teacher education is a strategy for helping learners to examine their progress in teaching (Sluijsmans and Prins, 2006) and be familiar with it before teaching in classrooms (Wen and Tsai, 2008). Teaching practice is an exercise used to expose student teachers to the practical aspects of teaching (Oluwatayo and Adebule, 2012). Although teaching practice is essential in teacher education (Jian, Odell, and Schwille, 2008;Oluwatayo and Adebule, 2012), attempts to improve it through early assessment are not widely reported (Charalambous, Hill and Ball, 2011).…”
Section: Peer Assessment Of Performance In Teacher Educationmentioning
confidence: 99%
“…Teaching practice is an exercise used to expose student teachers to the practical aspects of teaching (Oluwatayo and Adebule, 2012). Although teaching practice is essential in teacher education (Jian, Odell, and Schwille, 2008;Oluwatayo and Adebule, 2012), attempts to improve it through early assessment are not widely reported (Charalambous, Hill and Ball, 2011).…”
Section: Peer Assessment Of Performance In Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching practice is an integral component of teacher education programme (Ekundayo, Alonge, Kolawole & Ekundayo, 2014;Oluwatayo;Adebule, 2012, Mudzielwana & Maphosa, 2014). It is a basic requirement for all students of the faculty of education in 300 and 400 levels, each lasting for a period of six weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Preservice teachers' instructional effectiveness. One of a few studies regarding preservice teachers' instructional effectiveness was conducted by Oluwatayo and Adebule (2012). This study examined student teachers' teaching performance in secondary schools and found that gender and teaching experience were not correlated with teaching performance.…”
Section: Instructional Effectivenessmentioning
confidence: 99%